To solve the quadratic equation \( 3x^2 + 2x - 8 = 0 \) using factoring by grouping, let's first rewrite it:
-
We need to factor by grouping. We recognize that there are two pairs of terms in the expression. First, we derive the grouping based on the terms in the equation.
-
We can find the GCF (Greatest Common Factor). In this case, we can organize as:
\( 3x^2 + 6x - 4x - 8 = 0 \)
Splitting \( 2x \) into \( 6x \) and \( -4x \) allows us to factor it by grouping.
-
Now grouping the terms: \((3x^2 + 6x) + (-4x - 8) = 0\)
-
Taking out the GCF from each group: \[ 3x(x + 2) - 4(x + 2) = 0 \]
This implies that Martin has the correct factorization. Upon analyzing the provided options:
-
The first option is: \[ 3x(x+2)−4(x−2)=0 \] (Incorrect)
-
The second option is: \[ 3x(x+2)+4(x+2)=0 \] (Incorrect)
-
The third option is: \[ 3x(x+2)−4(x+2)=0 \] (Correct)
-
The fourth option is: \[ x(3x+6)+4(x+2)=0 \] (Incorrect)
Therefore, the missing part of Martin's work is:
\[ 3x(x+2)−4(x+2)=0 \] (option 3)